2018
DOI: 10.1186/s12913-017-2779-x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health services (SRHS) for adolescents in Enugu state, Nigeria: a mixed methods approach

Abstract: BackgroundAvailability and accessibility of sexual and reproductive health services for adolescents are very crucial for prevention and control of sexual and reproductive health problems. These services also play vital roles in the promotion of adolescents’ sexual and reproductive health generally. The main purpose of the study was to determine the availability and accessibility (geographical and financial) of sexual and reproductive health services (SRHS) among adolescents in Enugu State, Nigeria.MethodsA mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
93
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 13 publications
15
93
4
Order By: Relevance
“…In addition to that, a predetermined health service package that is offered at a health facility as defined by the Rwanda Ministry of Health limit facilities at offering some SRH services. These results differ from findings in Nigeria, where they reported that female condoms were available in almost all health facilities included in their study (14).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition to that, a predetermined health service package that is offered at a health facility as defined by the Rwanda Ministry of Health limit facilities at offering some SRH services. These results differ from findings in Nigeria, where they reported that female condoms were available in almost all health facilities included in their study (14).…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the study results, Rwanda is doing well in availing SRH services to help adolescents access them, but our results revealed that the SRH services provision were designed for the general population, without specialized adolescents SRH health providers and this comprehensive limit accessibility. Our results agree with previous studies conducted in Nigeria, Rwanda, and Kenya that also reported that SRH services were not mainly designed for adolescent's use (9,14,23). The study data reveals that some of the services are not available in health facilities due to being underutilized, such was the case with female condoms.…”
Section: Discussionsupporting
confidence: 92%
“…LARC requires a visit to the health facility for insertion and removal. The low utilization of clinics for uptake and use of contraception by adolescents and young persons in Nigeria [37][38][39] will likely be a barrier for LARC access by SIYP. Poor attention paid to the SRH needs of SIYP will further limit their use of healthcare services to address their SRH needs.…”
Section: Discussionmentioning
confidence: 99%
“…Like other most SSA countries, adolescents in Rwanda still face various challenges while seeking or trying to access SRH services such as limited availability or no specialized trained health care provider capable of catering adolescents' needs [14]. The government of Rwanda has been putting mechanisms and policies in place that would enable access to sexual and reproductive services for young adults since 2010 [15].…”
Section: Introductionmentioning
confidence: 99%
“…The government of Rwanda has been putting mechanisms and policies in place that would enable access to sexual and reproductive services for young adults since 2010 [15]. However, there is still evidence of increasing unwanted teen pregnancies, risky sexual behaviors, lack of comprehensive knowledge of SRH, and HIV risks among adolescents [14], [16], [17]. There is a gap in knowledge about provision of SRH services to adolescents in urban settings in Rwanda.…”
Section: Introductionmentioning
confidence: 99%